Planned mode of birth after previous caesarean section and special educational needs in childhood: a population‐based record linkage cohort study. (28th July 2021) - Fitzpatrick, KE; Kurinczuk, JJ; Quigley, MA
Abstract : Objective: To investigate the association between planned mode of birth after previous caesarean section and a child's risk of having a record of special educational needs (SENs). Design: Population‐based cohort study. Setting: Scotland. Population: A cohort of 44 892 singleton children born at term in Scotland between 2002 and 2011 to women with one or more previous caesarean sections. Methods: Linkage of Scottish national health and education data sets. Main outcome measures: Any SENs and specific types of SEN recorded when a child was aged 4–11 years and attending a Scottish primary or special school. Results: Children born following planned vaginal birth after previous caesarean (VBAC) compared with elective repeat caesarean section (ERCS) had a similar risk of having a record of any SENs (19.24 versus 17.63%, adjusted risk ratio aRR 1.04, 95% CI 0.99–1.09) or specific types of SEN. There was also little evidence that planned VBAC with or without labour induction compared with ERCS was associated with a child's risk of having a record of any SENs (21.42 versus 17.63%, aRR 1.09, 95% CI 1.01–1.17 and 18.78 versus 17.63%, aRR 1.03, 95% CI 0.98–1.08, respectively) or most types of SEN. However, an increased risk of sensory impairment was seen for planned VBAC with labour induction compared with ERCS (1.18 versus 0.78%, risk difference 0.4%, adjusted odds ratio aOR 1.60, 95% CI 1.09–2.34). Conclusions: This study provides little evidence of an association between planned mode of birth after previous caesarean and SENs in childhood beyond a small absolute increased risk of sensory impairment seen for planned VBAC with labour induction. This finding may be the result of performing multiple comparisons or residual confounding. The findings provide valuable information to manage and counsel women with previous caesarean section concerning their future birth choices. Tweetable abstract: There is little evidence planned mode of birth after previous caesarean section is associated with special educational needs in childhood. Tweetable abstract: There is little evidence planned mode of birth after previous caesarean section is associated with special educational needs in childhood.